Composite positive electrode slurry, positive electrode plate, preparation method of positive electrode plate and all-solid-state battery

By adding low-surface energy substances to the composite positive electrode slurry to block the contact between the sulfide electrolyte and moisture in the air, the problem of poor stability of all solid batteries is solved, and higher battery stability and cycling performance are achieved.

CN119447308AActive Publication Date: 2025-02-14SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411737131.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing all-solid state batteries have poor stability, especially the sulfide solid electrolytes are sensitive to air and are prone to react with moisture to form toxic gases, resulting in attenuation of electrochemical properties.

Method used

The composite positive electrode slurry is added with low surface energy substances, such as fluorinated polysiloxane, as a polymer with excellent hydrophobic properties, to block the contact between the sulfide electrolyte and the moisture in the air and reduce the formation of toxic gases.

Benefits of technology

By adding low-surface energy substances, the stability of the battery is improved, the structural damage of the sulfide electrolyte is reduced, and the circulation and rate performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447308A_ABST
    Figure CN119447308A_ABST
Patent Text Reader

Abstract

The invention relates to the field of all-solid-state lithium ion batteries, in particular to composite positive electrode slurry, a positive electrode plate, a preparation method of the positive electrode plate and an all-solid-state battery, the slurry comprises a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low-surface-energy substance, and the low-surface-energy substance is a substance with a contact angle larger than 90 degrees; the low surface energy substance is one or more of fluorinated polysiloxane, polysiloxane, octadecanoic acid and stearic acid. The low-surface-energy substance provided by the invention belongs to a polymer with excellent hydrophobicity. When the polymer is mixed in the slurry, the contact between sulfide electrolyte and water in air can be blocked, the generation of H2S toxic gas is reduced, and the structural damage of sulfide is reduced, so that the stability of the battery is improved. In addition, the preparation method is simple to operate when directly mixing in the slurry, and is beneficial to large-scale tests.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of preparation of all-solid-state lithium-ion battery materials, and specifically, to a composite positive electrode slurry, a positive electrode plate and a preparation method thereof, and an all-solid-state battery. Background Art

[0002] Sulfide solid electrolytes have attracted much attention due to their high ionic conductivity and good mechanical properties (easy to eliminate grain boundary impedance), and are currently commonly used electrolyte materials for solid-state batteries. However, sulfide solid electrolytes are very sensitive to air and have poor electrochemical stability. Among them, sulfide electrolytes containing the element P are extremely sensitive to moisture in the air. When exposed to air, hydrogen sulfide is easily generated, causing the solid electrolyte to fail. At the same time, the composition, crystal structure and morphology of the sulfide electrolyte change, and the electrochemical properties such as ionic conductivity are greatly attenuated; the cost of material synthesis, processing, transportation and battery preparation is increased.

[0003] At present, some researchers in the industry have partially or completely replaced the P element with metal elements to obtain electrolytes with higher air stability and higher ion mobility. Some researchers have also constructed a coating layer on the surface of sulfide particles, using air-stable materials or even hydrophobic materials as a modification method for the coating layer of sulfide particles. However, the ion conductivity of the prepared coating layer is much lower than that of the sulfide electrolyte material, and the hydrophobic molecular layer that does not contain lithium as the coating layer has no lithium ion transmission ability, which greatly limits the high lithium ion conductivity of the sulfide. In particular, the fluorinated polysiloxane material coated on the solid electrolyte will hinder the Li + The conduction slows down the reaction kinetics, and the process of coating the fluorinated polysiloxane on the solid electrolyte is complicated and costly, which is not conducive to scale-up experiments.

[0004] Therefore, how to improve the stability of all-solid-state batteries while ensuring battery performance remains a difficult problem that scientific researchers are eager to solve. Summary of the invention

[0005] In order to solve the technical problem of poor stability of all-solid-state batteries in the prior art, the present invention provides a composite positive electrode slurry, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery. The positive electrode sheet prepared by the composite positive electrode slurry can produce an all-solid-state battery with better performance and stability. The technical solution of the present invention is implemented as follows:

[0006] A first aspect of the present invention provides a composite positive electrode slurry, which includes a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low surface energy substance; the low surface energy substance is a substance with a contact angle greater than 90°.

[0007] In one embodiment, the mass of the low surface energy substance is set to W1, the total mass of the positive electrode active material, the first solid electrolyte, the conductive agent, the binder and the low surface energy substance is set to W2, and the mass percentage of W1 to W2 is 0.1% to 1%.

[0008] In one embodiment, the positive electrode active material is one or more of lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt aluminum oxide (NCA) and lithium rich manganese-based oxide (LRMO).

[0009] In one embodiment, the first solid electrolyte material is a sulfide solid electrolyte.

[0010] Li 6 PS 5 Cl(LPSC) and Li 10 G 2 S 12 (LGPS) or more;

[0011] In one embodiment, the conductive agent material is one or more of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers, and graphene;

[0012] In one embodiment, the binder material is one or more of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), nitrile rubber (NBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA);

[0013] In one embodiment, the low surface energy material is one or more of fluorinated polysiloxane, polysiloxane, octadecanoic acid, and stearic acid.

[0014] A second aspect of the present invention provides a composite positive electrode plate, wherein the composite positive electrode plate is made of the composite positive electrode slurry described in the first aspect; the composite positive electrode plate also includes a positive electrode current collector.

[0015] A third aspect of the present invention provides a method for preparing a composite positive electrode sheet, the method comprising the following steps:

[0016] S1, mixing a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low surface energy substance and adding the mixture to a solvent;

[0017] S2, repeatedly stirring and mixing at high speed and removing bubbles to form a mixed slurry;

[0018] S3, coating the mixed slurry on the positive electrode current collector and drying it;

[0019] S4, then rolling and slitting to obtain the positive electrode sheet.

[0020] In one embodiment, the solvent is one or more of toluene, isobutyl isobutyrate, butyl butyrate, hexyl butyrate, diisobutyl ketone, and anisole.

[0021] In one embodiment, in the method for preparing the composite positive electrode sheet, after the composite positive electrode slurry and the solvent are mixed, the solid content is 50% to 70%.

[0022] In one embodiment, the positive electrode current collector is aluminum foil with a thickness of 12 μm, and the positive electrode plate has a thickness of 0.1 μm to 200 μm.

[0023] In the method for preparing the composite positive electrode plate, the composite positive electrode slurry and the solvent are mixed under high-speed stirring in a drying room, and then defoamed under stirring, and the mixing is repeated to form a slurry.

[0024] In one embodiment, in the preparation method of the composite positive electrode plate, mixing is performed at a speed of 1500rpm to 3000rpm for 5min to 30min in a drying room at -50°C to -30°C with a high-speed stirrer, followed by defoaming at a speed of 400rpm to 1000rpm for 3min to 10min, and the mixing is repeated twice to form a uniform mixed slurry.

[0025] In one embodiment, in the method for preparing the composite positive electrode sheet, the mixed slurry is coated on the positive electrode collector, dried at 60° C. to 120° C. for 8 h to 16 h, and then rolled and cut to obtain the positive electrode sheet.

[0026] The fourth aspect of the present invention proposes an all-solid-state battery, which includes the positive electrode sheet, the negative electrode sheet, and the second solid electrolyte proposed in the second and third aspects of the present invention.

[0027] Beneficial effects of the present invention:

[0028] The present invention provides a composite positive electrode slurry for an all-solid-state battery, wherein the low surface energy substance added is a polymer with excellent hydrophobic properties. The polymer is mixed in the slurry to block the contact between the sulfide electrolyte and the water in the air, thereby reducing the H 2 The production of toxic S gas can be reduced, and the structural damage of sulfide can be reduced, thereby improving the stability of the battery. In addition, it is easy to mix it directly into the slurry, which is conducive to large-scale testing. Specifically, the first discharge specific capacity of the prepared positive electrode sheet is higher, and the capacity retention rate is higher after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only one embodiment of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] The same parts are denoted by the same reference numerals. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the drawings, and the words "bottom" and "top", "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively.

[0031] Figure 1 This is a picture of the static contact angle with water in Example 1 of the present invention; as the only figure of the present invention, this figure is also designated as the abstract figure. Specific embodiments

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0034] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0035] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0036] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0037] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood as modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0038] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0039] Sulfide solid electrolytes are very sensitive to air and have poor electrochemical stability. Among them, sulfide electrolytes containing P elements are extremely sensitive to moisture in the air. When exposed to air, hydrogen sulfide is easily generated, causing the solid electrolyte to fail. At the same time, the composition, crystal structure and morphology of the sulfide electrolyte change, and the electrochemical properties such as ionic conductivity are greatly attenuated, increasing the cost of material synthesis, processing, transportation and battery preparation.

[0040] At present, some researchers in the industry have partially or completely replaced the P element with metal elements to obtain electrolytes with higher air stability and higher ion mobility. Some researchers have also constructed a coating layer on the surface of sulfide particles, using air-stable materials or even hydrophobic materials as a modification method for the coating layer of sulfide particles. However, the ion conductivity of the prepared coating layer is much lower than that of the sulfide electrolyte material, and the hydrophobic molecular layer that does not contain lithium as the coating layer has no lithium ion transmission ability, which greatly limits the high lithium ion conductivity of the sulfide. In particular, the fluorinated polysiloxane material coated on the solid electrolyte will hinder the Li + The conduction slows down the reaction kinetics, and the process of coating the fluorinated polysiloxane on the solid electrolyte is complicated and costly, which is not conducive to scale-up experiments.

[0041] In order to solve the above problems, the present invention proposes a technical solution, which is to add a low surface energy substance, a polymer with excellent hydrophobic properties, to the composite positive electrode slurry. This polymer mixed in the slurry can block the contact between the sulfide electrolyte and the water in the air, reduce H 2 S can reduce the generation of toxic gas and reduce the structural damage of sulfide, thus improving battery stability. In addition, it is easy to operate by directly mixing it into the slurry, which is conducive to large-scale testing.

[0042] A first aspect of the present invention provides a composite positive electrode slurry, which includes a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low surface energy substance; the low surface energy substance is a substance with a contact angle greater than 90°.

[0043] In one embodiment, the mass of the low surface energy substance is set to W1, the total mass of the positive electrode active material, the first solid electrolyte, the conductive agent, the binder and the low surface energy substance is set to W2, and the mass percentage of W1 to W2 is 0.1% to 1%.

[0044] In one embodiment, the mass percentage of W1 and W2 may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. The above values ​​are only examples, and the present invention does not impose any limitation thereto.

[0045] In one embodiment, the positive electrode active material is one or more of lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt aluminum oxide (NCA) and lithium rich manganese-based oxide (LRMO).

[0046] In one embodiment, the first solid electrolyte material is a sulfide solid electrolyte.

[0047] Li6 PS 5 Cl(LPSC) and Li 10 G 2 S 12 (LGPS) or more;

[0048] The main advantages of sulfide solid electrolytes include high ionic conductivity, high energy density, good safety performance, long cycle life and fast charging capability.

[0049] In one embodiment, the conductive agent material is one or more of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers, and graphene;

[0050] In one embodiment, the binder material is one or more of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), nitrile rubber (NBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA);

[0051] In one embodiment, the low surface energy material is one or more of fluorinated polysiloxane, polysiloxane, octadecanoic acid, and stearic acid. In the present invention, the low surface energy material is fluorinated polysiloxane.

[0052] A small amount of low surface energy substance - fluorinated polysiloxane is additionally introduced into the composite positive electrode slurry. By introducing perfluoroalkyl groups on the side chains or branches of polysiloxane, the advantages of organosilicon and organic fluoride can be organically combined, so that fluorinated polysiloxane has both low surface energy similar to fluorine and the softness of organosilicon, thereby obtaining a polymer with excellent hydrophobic properties.

[0053] A second aspect of the present invention provides a composite positive electrode plate, wherein the composite positive electrode plate is made of the composite positive electrode slurry described in the first aspect; the composite positive electrode plate also includes a positive electrode current collector.

[0054] A third aspect of the present invention provides a method for preparing a composite positive electrode sheet, the method comprising the following steps:

[0055] S1, mixing a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low surface energy substance and adding the mixture to a solvent;

[0056] S2, repeatedly stirring and mixing at high speed and removing bubbles to form a mixed slurry;

[0057] S3, coating the mixed slurry on the positive electrode current collector and drying it;

[0058] S4, then rolling and slitting to obtain the positive electrode sheet.

[0059] In one embodiment, the solvent is one or more of toluene, isobutyl isobutyrate, butyl butyrate, hexyl butyrate, diisobutyl ketone, and anisole.

[0060] In one embodiment, in the method for preparing the composite positive electrode sheet, after the composite positive electrode slurry and the solvent are mixed, the solid content is 50% to 70%.

[0061] Solid content refers to the percentage of solid components in the slurry.

[0062] In one embodiment, the solid content of the positive electrode active material, the first solid electrolyte, the conductive agent, the binder, the low surface energy material and the solvent after mixing can be selected to be 50%, 55%, 60%, 65%, 70%, etc. The above values ​​are only examples, and the present invention does not impose any limitation on this.

[0063] In one embodiment, the positive electrode current collector is aluminum foil with a thickness of 12 μm, and the positive electrode plate has a thickness of 0.1 μm to 200 μm.

[0064] In one embodiment, the thickness of the positive electrode plate can be selected to be 0.1 μm, 5 μm, 10 μm, 25 μm, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm, or 200 μm. The above values ​​are only examples and the present invention does not impose any limitation thereto.

[0065] In the method for preparing the composite positive electrode plate, the composite positive electrode slurry and the solvent are mixed under high-speed stirring in a drying room, and then defoamed under stirring, and the mixing is repeated to form a slurry.

[0066] In one embodiment, in the preparation method of the composite positive electrode slurry, mixing is performed at a speed of 1500rpm to 3000rpm for 5min to 30min in a drying room at -50℃ to -30℃ with a high-speed stirrer, followed by defoaming at a speed of 400rpm to 1000rpm for 3min to 10min, and the mixing is repeated twice to form a uniform mixed slurry.

[0067] In one embodiment, the temperature in the drying room can be selected as -50°C, -45°C, -40°C, -35°C, -30°C, etc., the speed of the high-speed stirrer can be selected as 1500rpm, 2000rpm, 2500rpm, 3000rpm, etc., the mixing time can be selected as 5min, 10min, 15min, 20min, 25min, 30min, etc.; the subsequent defoaming speed can be selected as 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, etc., and the defoaming time can be selected as 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, etc. The above values ​​are only examples, and the present invention does not make any limitation thereto.

[0068] In one embodiment, in the preparation method of the composite positive electrode sheet, the mixed slurry is coated on the positive electrode collector, dried at 60°C to 120°C for 8h to 16h, and rolled and cut after drying to obtain the positive electrode sheet. In one embodiment, the temperature for drying the composite positive electrode sheet can be selected from 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the drying time can be selected from 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, etc. The above values ​​are only examples, and the present invention does not impose any limitation on this.

[0069] The fourth aspect of the present invention proposes an all-solid-state battery, which includes the positive electrode sheet, the negative electrode sheet, and the second solid electrolyte proposed in the second and third aspects of the present invention.

[0070] The negative electrode sheet preparation method of the present invention comprises the following steps: 95% (by mass) of negative electrode active material (the mass percentage of graphite: silicon oxide is 80%:20%), 2% of solid electrolyte, 2% of conductive agent and 1% of binder are mixed to form a negative electrode slurry, the negative electrode slurry is coated on a negative electrode collector (copper foil), and after drying, the negative electrode sheet is obtained by rolling and cutting.

[0071] The solid electrolyte layer preparation method of the present invention: the solid electrolyte layer is composed of a second solid electrolyte and a binder (PTFE); the mass ratio of the two is 99:1, and the film thickness is 200 μm.

[0072] In one embodiment, the second solid electrolyte material is a sulfide solid electrolyte.

[0073] Li 6 PS 5 Cl(LPSC) and Li 10 G 2 S 12 (LGPS) or more;

[0074] The method for preparing an all-solid-state battery of the present invention comprises stacking a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet in sequence and encapsulating them in an aluminum-plastic film. After vacuum is applied to the aluminum-plastic film, the film is sealed and the battery is isostatically pressed at 460 MPa to obtain an all-solid-state lithium-ion battery.

[0075] The embodiments of the present invention will be described in more detail below through examples and comparative examples, wherein all examples and comparative examples are lithium ion battery sample groups prepared by the same process.

[0076] In order to intuitively and comprehensively reflect the advantages of the present invention, all embodiments and comparative examples record or perform the following tests: contact angle test, 0.1C first discharge specific capacity test, and 0.33C capacity retention test after 100 cycles.

[0077] It should be noted that the embodiments of the present invention are not limited to these examples.

[0078] Example 1

[0079] 1. Preparation of positive electrode

[0080] 1) LiNi positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), sulfide solid electrolyte Li 6 PS 5 Cl, conductive agent carbon nanofiber, binder NBR and low surface energy material fluorinated polysiloxane are mixed, the mass of the low surface energy material is set to W1, the total mass of the positive electrode active material, the first solid electrolyte, the conductive agent, the binder and the low surface energy material is set to W2, the mass percentage of W1 and W2 is 0.5%, and it is added to the solvent isobutyl isobutyrate, and the solid content is 60%.

[0081] 2) In a drying room (-40°C), the above raw materials were mixed with a high-speed stirrer at 2000 rpm for 10 min, and then defoamed at 500 rpm for 5 min. The above mixing operation was repeated twice to form a uniform mixed slurry.

[0082] 3) Then, in a drying room, the slurry is coated on the positive electrode current collector with a scraper, transferred to a vacuum oven, and dried at 80°C for 12 hours. After drying, the positive electrode sheet is obtained by rolling and slitting. The positive electrode current collector is aluminum foil with a thickness of 12 μm; the thickness of the positive electrode sheet is 100 μm.

[0083] 2. Preparation of negative electrode sheet

[0084] 95% negative electrode active material (graphite: silicon oxygen = 80%: 20%), 2% solid electrolyte Li 6PS 5 Cl, 2% conductive carbon black and 1% binder PAA are mixed to form negative electrode slurry, which is then coated on a negative electrode current collector (copper foil), dried, rolled and cut to obtain negative electrode sheets.

[0085] 3. Preparation of solid electrolyte layer

[0086] The solid electrolyte layer is composed of the second solid electrolyte Li 6 PS 5 Cl and binder PTFE; the mass ratio of the two is 99:1, and the membrane thickness is 200μm.

[0087] 4. Preparation of all-solid-state batteries

[0088] The positive electrode sheet, the solid electrolyte layer and the negative electrode sheet are stacked and packaged in an aluminum-plastic film in sequence. After vacuum is applied to the aluminum-plastic film, it is sealed and the battery is isostatically pressed at 460 MPa to obtain an all-solid-state lithium-ion battery.

[0089] After measuring the contact angle of the positive electrode sheet (such as Figure 1 The composite positive electrode sheet is then used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0090] Example 2

[0091] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.1%.

[0092] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0093] Example 3

[0094] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.2%.

[0095] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0096] Example 4

[0097] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.3%.

[0098] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0099] Example 5

[0100] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.4%.

[0101] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0102] Example 6

[0103] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.6%.

[0104] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0105] Example 7

[0106] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.7%.

[0107] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0108] Example 8

[0109] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.8%.

[0110] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0111] Example 9

[0112] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 0.9%.

[0113] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0114] Example 10

[0115] Example 1 provides a composite positive electrode slurry, a positive electrode sheet preparation method and an all-solid-state battery, which are the same as the low surface energy material and preparation method used in Example 1, and the only difference from Example 1 is that the mass percentage of W1 and W2 is 1%.

[0116] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0117] Comparative Example 1

[0118] The method for preparing the positive electrode sheet is the same as that used in Example 1, and the difference from Example 1 is that the low surface energy material fluorinated polysiloxane is not added.

[0119] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0120] Comparative Example 2

[0121] The method for preparing the positive electrode sheet is the same as that used in Example 1, and the difference from Example 1 is that the mass percentage of W1 and W2 is 0.02%.

[0122] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0123] Comparative Example 3

[0124] The method for preparing the positive electrode sheet is the same as that used in Example 1, and the difference from Example 1 is that the mass percentage of W1 and W2 is 1.2%.

[0125] After measuring the contact angle of the above-mentioned positive electrode sheet, the composite positive electrode sheet is used in an all-solid-state battery and its performance is tested. The test results are shown in Table 1.

[0126] The positive electrode sheets prepared in the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 3 were used to prepare all-solid-state batteries, and the performance of the all-solid-state batteries was tested. The test results are shown in Table 1 below:

[0127] Contact angle measurement method:

[0128] The contact angle is measured using the static contact angle method. A certain amount of water is dropped on the solid surface, the shape of the drop is observed through a microscope, and the angle between the edge of the drop and the solid interface is measured.

[0129] First discharge capacity test:

[0130] At room temperature (25°C), the fully charged battery was discharged at a constant current of 0.1C to a cut-off voltage of 2.5V to obtain the first discharge capacity.

[0131] Cyclic battery capacity retention rate:

[0132] At a temperature of 45°C, charge at a current of 0.33C to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, then discharge at a current of 0.33C to a cut-off voltage of 2.5V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 100 charge and discharge cycles.

[0133] Table 1. Performance test results of all-solid-state batteries

[0134]

[0135] According to the above table, by comparing Examples 1 to 10 with Comparative Examples 1 to 3, the present invention provides a composite positive electrode slurry for an all-solid-state battery, wherein the added low surface energy substance is a polymer with excellent hydrophobic properties. The polymer is mixed in the slurry to block the contact between the sulfide electrolyte and the water in the air, reduce the generation of H2S toxic gas, reduce the structural damage of the sulfide, and thus improve the battery stability. In addition, directly mixing it in the slurry is simple to operate, which is conducive to large-scale testing.

[0136] In Examples 1 to 10, by adding low surface energy substances to the positive electrode materials, the contact angle increases with the increase in the amount of low surface energy substances added; the 0.1C first discharge specific capacity and the capacity retention rate after 100 cycles at 0.33C are both in a trend of first increasing and then decreasing, reaching a peak value when the addition amount is 0.5%. When the contact angle becomes larger, it means that the wettability of the liquid on the solid surface becomes worse, that is, the hydrophobicity is enhanced and the hydrophilicity is weakened. Therefore, the low surface energy substance can enhance the hydrophobicity of the battery, and improve the cycle performance and rate performance.

[0137] Comparing Example 1 with Comparative Examples 1 to 3, when no low surface energy material is added, the hydrophobic performance is significantly weakened, and the rate performance and cycle performance reach the lowest. From Comparative Example 2, it can be seen that when the addition amount is 0.02%, the overall performance of the battery is slightly improved, while when excessive addition is made, the battery performance will decrease instead.

[0138] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite positive electrode slurry, characterized in that: The invention comprises a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low surface energy substance; the low surface energy substance is a substance with a contact angle greater than 90°.

2. The composite positive electrode slurry according to claim 1, characterized in that The mass of the low surface energy substance is set to W1, the total mass of the positive electrode active material, the first solid electrolyte, the conductive agent, the binder and the low surface energy substance is set to W2, and the mass percentage of W1 to W2 is 0.1% to 1%.

3. The composite positive electrode slurry according to claim 1, characterized in that: The positive electrode active material is one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide and lithium-rich manganese-based oxide.

4. The composite positive electrode slurry according to claim 1, characterized in that The low surface energy substance is one or more of fluorinated polysiloxane, polysiloxane, octadecanoic acid and stearic acid.

5. A composite positive electrode sheet, characterized in that: Made from the composite positive electrode slurry according to any one of claims 1 to 4.

6. The composite positive electrode sheet according to claim 5, characterized in that: The composite positive electrode sheet also includes a positive electrode current collector.

7. The method for preparing a composite positive electrode sheet according to claims 5 to 6, characterized in that: The method comprises the following steps: S1, mixing a positive electrode active material, a first solid electrolyte, a conductive agent, a binder and a low surface energy substance and adding the mixture to a solvent; S2, repeatedly stirring and mixing at high speed and removing bubbles to form a mixed slurry; S3, coating the mixed slurry on the positive electrode current collector and drying it; S4, then rolling and slitting to obtain the positive electrode sheet.

8. The method for preparing a composite positive electrode sheet according to claim 7, characterized in that: After the composite positive electrode slurry is mixed with the solvent, the solid content is 50% to 70%. 9 . The method for preparing a composite positive electrode sheet according to claim 7 , wherein the thickness of the positive electrode sheet is 0.1 μm to 200 μm.

10. An all-solid-state battery, characterized in that: It comprises the positive electrode sheet, the negative electrode sheet and the second solid electrolyte as described in claims 5 to 8.

Citation Information

Patent Citations

  • Super-hydrophobic material capable of conducting lithium ions as well as preparation method and application thereof

    CN112701345A

  • Coated modified silicon carbon negative electrode material as well as preparation method and application thereof

    CN118825278A

  • All-solid battery and manufacturing method thereof

    JP2024033235A

  • All-solid-state battery

    US20240178394A1